Vault design of highway tunnels based on the driver's physiological characteristics. Issue 3 (4th May 2022) - Ye, Fei; Ying, Kai-Chen; Liang, Xiao-Ming; Su, En-Jie; Liang, Xing; Wei, Yan-Chun
ABSTRACT: Most studies about tunnel environments focus on the adjustment of brightness in tunnels and pay little attention to the decoration of the walls. This study is based on a highway tunnel in Jilin province, China. Five design schemes (white, gray, dark-blue, light-yellow, and blue sky with white clouds) were selected for the tunnel vaults. The experiment was conducted on a self-developed driving simulation platform. Pupil diameter and heart rate growth (HRG) were proposed to analyze the driving comfort. A SMI eye tracker and a Polar heart-rate belt were employed to record the pupil diameter and heart rate, respectively. The results indicate that the color of the tunnel vault considerably influences the pupil diameter and HRG of a driver. The degrees of emotional fluctuation and psychological tension is higher for drivers in dark-color environments than in light-color environments. Therefore, light colors must be prioritized when designing tunnel vaults. The results also indicate that a tunnel vault in blue sky with white clouds is the most comfortable for drivers. This experiment provides a reference for the tunnel design. Graphical abstract: uf0001